Microstructural, Chemical and Mineralogical Analyses for Understanding the Geotechnical Properties of Clayey Soils - KIKI, Yvette Tankpinou; SAIYOURI, Nadia; GBAGUIDI, Victor (My University, 2016)
This paper presents a study research in the laboratory of three clayey soils from the depression of the Lama, a tropical climate area where disorders appear on construction and roads. Samples were tested to establish the relationship between their mineralogy and their geotechnical properties. On the three clayey soils, analyses were performed to characterize the macroscopic behavior (physical tests, free swelling test and compressibility tests) and the microstructural, chemical and mineralogical characterizations by thermal analysis, chemical analysis, X-Ray diffraction, Scanning Electron Microscopy observations complementary X-ray EDS analyses. At first glance, the results of physical and compressibility tests appear not to be consistent with the free swelling test results. Indeed, these results highlighted differences in the behaviors of the samples because the swelling potential revealed by the results of physical and compressibility test does not follow the same trend as the one given by the free swelling test result. The main clay minerals in the studied clayey soils varied from fibrous clays (palygorskite) to bestknown clays such as smectite and kaolinite. Microstructural, chemical and mineralogical analyses allowed to understand and explain the different trends obtained by the different types of geotechnical characterization tests of studied clayey soils.
Keywords: Geotechnical; Mineralogical; Microstructural; Free Swelling Index; Smectite; Palygorskite; Clayey Soils